Medical physics practice in the next decade - Paliwal, Bhudatt (Medknow Publications, 2006)
Impressive advances in computers and materials science have fueled a broad-based confluence of basic science breakthroughs. These advances are making us reformulate our learning, teaching and credentialing methodologies and research and development frontiers. We are now in the age of molecular medicine. In the entire field of health care, a paradigm shift from population-based solutions to individual specific care is taking place. These trends are reshaping the practice of medical physics. In this short presentation, examples are given to illustrate developments in image-guided intensity-modulated and adaptive helical tomotherapy, enhanced application of intensity modulation radiotherapy (IMRT) using adaptive radiotherapy and conformal avoidance. These advances include improved normal tissue sparing and permit dose reconstruction and verification, thereby allowing significant biologically effective dose escalation and reduced radiation toxicity. The intrinsic capability of helical TomoTherapy for megavoltage CT imaging for IMRT image-guidance is also discussed. Finally developments in motion management are described.